(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
Although the term animal assisted therapy is relatively new, the use of animals to overcome disease or a condition in humans is not a new idea. The earliest use of animals for therapeutic purposes was noticed in Belgium, where animals and humans were rehabilitated together, and animals were an important part of human natural therapy. The application of various therapies and activities with children with disabilities in order to improve their overall condition and the implementation of daily activities is expanding. One of the modern approaches in the treatment of children with disabilities is canine assisted therapy and focuses on improving a person’s physical, cognitive and socio-emotional functioning. Our research was organized in a quasi-experimental format, there were control and experimental groups, including children with motor disorders, speech problems and children with behavioural problems. The control group underwent classical treatment with a special educator and rehabilitator, while the experimental group received dog assisted therapy. Researches indicate that the presence of a dog during the therapies helps children improve their mood, increases their will to actively participate, have easier emotional expression, improves or overcomes speech disorders, encourages communication, improves psychomotor development and achieves a range physiological benefits.